Special Consideration in the Management of Hump Noses in Asians - Jang, Yong Ju; Moon, Hyun (Facial Plastic Surgery, 2020)
Although not as prevalent as in Caucasian rhinoplasty, correction of a hump nose also poses a significant problem for East Asian rhinoplasty. The hump noses in East Asians can be classified as generalized humps, isolated humps, and relative humps with a low tip. Appropriate management of the Asian hump nose demands a good understanding of the anatomical characteristics unique to East Asians. As the East Asians generally prefer to have a nose with a prominent tip and well-augmented nasal dorsum, the concept of redistribution is significant in managing convex dorsum of the East Asians. Hump reduction should be done in a conservative and incremental manner, including careful removal of the bony cap and cartilaginous hump. Tip augmentation using a septal extension graft is an essential maneuver to achieve an aesthetically pleasing tip height, which has a tremendous impact on the overall aesthetic outcome. Midvault reconstruction, dorsal augmentation, and camouflage are additional key elements for the success of the operation. Complications such as undercorrection and dorsal irregularities are not uncommon, requiring surgeons to take utmost care to address them.
Keywords: hump nose; asian; tip augmentation; dorsal augmentation; camouflage